PROSES KREATIF PEMERANAN RUTH MARINI DALAM MONOLOG WANCI KARYA IMAS SOBARIA - Hudha, Tafsir (Institut Seni Indoensia Surakarta, 2017)
Ruth Marini’s creative process in performing Wanci Monologue by Imas Sobariah, was Ruth Marini’sattempt in exploring various stages of work or creativity in the role of Icih as the main character in WanciMonologue. As a consequence of the singular characterization of the monologue, the subsequent searchwas directed at the specific creativity that Ruth Marini had done in transforming the Icih character to therole of several other figures as a result of Icih’s narrative of her past which later spawned tragic stories inher life. The search for this creative process was thus focused on the creative ways that Ruth Marinipursued in developing role play or acting, including the stimulants that supported the maximal acting ofRuth Marini in the Imas Sobariah’s Wanci Monologue.Stimulants that were excavated for the developmentof Ruth Marini’s acting was traced through various views of Ruth Marini works of art, especially RuthMarini’s perspective on acting in a monologue. The conclusion of the views of art and acting would bepreceded by exploring some of Ruth Marini’s works of art through previous performances to understandRuth Marini’s contributions to her artistic enrichment process, specifically to the development of actingthat was required in the Wanci Monologue by Imas Sobariah.Keywords: Monologue,art perspective, acting.